PRISON CONFLICT MANAGEMENT STRATEGY IN PREVENTING RIOTS - Riyanto (STIE Kusuma Negara, 2020)
In the implementation of formation there are still prisoners who are physically and mentally depressed, because of inhumane acts between fellow inmates or a crackdown by officers. As a result it can create security and order disturbances in prison. One of them is the riots that occurred in Lapas due to the response of treatment given by Lapas during prisoners undergoing guidance. Like the riot incident that was found in Langkat Narcotics Prison on May 16, 2019 which resulted from torture and ill-treatment of prisoners by officers. But there is a prison, the Class III prison in Cikarang which has a clean record of riots within prison in the 2016-2019 period. This research will raise the issue of how to form Lapas conflict management in order to prevent riots in Lapas. This study aims to determine the form of Lapas conflict management in order to prevent riots in Lapas. This research was conducted in Class III Prison Cikarang. This study uses a qualitative research approach. This research was conducted in October 2019. Data taken by observation, interview and document study techniques were then processed and analyzed qualitatively. The results of this study indicate that the Class III Prison in Cikarang has a form of conflict management that is able to create security and order and avoid the riots perpetrated by inmates.